Unbundling of the green bond market in the economic hubs of Africa: Case study of Kenya, Nigeria and South Africa. Issue 6 (1st November 2020) - Ngwenya, Nomhle; Simatele, Mulala Danny
ABSTRACT: Climate change is arguably one of the biggest challenges globally. In order for countries to meet the commitments of the Paris Agreement, climate investments need to be scaled up for adaptation and mitigation strategies. Green bonds are one of the most emerging climate finance mechanisms for large-scale climate projects and offer investment opportunities for many developing countries. Most developing countries are heavily reliant on climate funds which are insufficient. Hence, the urgent need to tap into emerging climate finances such as green bonds. Out of all the regions, Africa is expected to be the worst impacted by climate change and green bonds can contribute to the much needed climate finances. The growth of the green bond market has been observed in the economic hubs of the continent with countries such as Kenya, Nigeria and South Africa demonstrating huge potential in being active and contributing to the growth of the market. However, this paper recommends that for the green bond market to further expand in these countries and rest of the continent, there needs to be public–private partnerships fostered, integrated policies, political will as well as effective institutional frameworks.